Physical activity and academic performance in adolescents: chain mediation through self-regulation and self-efficacy with gender and urban–rural differences - Che, Li; Liu, Dachao; Tie, Chunyuan (Frontiers in Education, 2026)
BackgroundEmpirical evidence increasingly supports a positive association between physical activity and adolescent academic performance, yet most studies rely on single-mediator models and rarely examine serial mediation or demographic heterogeneity.MethodsUsing nationally representative data from the China Education Panel Survey (CEPS, 2014–2015), this investigation analyzed 8,037 secondary school students. Nested regression models were first estimated to assess the direct association between physical activity and academic performance. Structural equation modeling with bootstrap resampling was then applied to examine mediation pathways through self-regulation and self-efficacy, followed by multi-group analyses across gender and urban–rural subgroups.ResultsPhysical activity was positively associated with academic performance. Mediation analysis indicated that this association operated through self-regulation and self-efficacy, including a serial pathway of “physical activity → self-regulation → self-efficacy → academic performance.” Heterogeneity analysis further showed that this serial mediation was stronger for males than females and for rural students than urban students, with males and rural students relying more on self-regulation, whereas females and urban students showed a relatively greater contribution of self-efficacy.ConclusionPhysical activity enhances adolescents’ academic performance through psychological mechanisms such as self-regulation and self-efficacy, including a mediated pathway from self-regulation to self-efficacy. The strength and relative importance of these pathways vary by gender and urban/rural location: boys and rural students benefit more from self-regulation, while girls and urban students rely more on self-efficacy. Therefore, physical activities conducted in schools and homes should explicitly integrate training in self-regulation and self-efficacy into physical education classes and after-school activities, and be adjusted according to gender and environmental differences.